Fansubbing practices in Ukraine: Promoting national culture worldwide - Gach, Nataliia (Linguistics and Culture Review, 2021)
This research focuses on the analysis of the English non-professional subtitles of the Ukrainian films, produced by the amateur translators for whom English is a foreign language. Such exploration in the nature of fansubbing gives insights into the basic principles that define the notion of subtitling, examines the standards set to the audiovisual translation, and outlines the challenges fansubbers may face in the process of subtitling. The study is based on the following Ukrainian films of the second half of the XXth – beginning of the XXIst century: Chasing Two Hares (1961); Shadows of Forgotten Ancestors (1965); Prayer for Hetman Mazepa (2001). The analysis of the films is conducted on the syntactic, lexical, and grammatical levels, as well as on the level of fansubs screen presentation (spatial and temporal parameters). The study discusses fansubbers’ translation decisions from the perspective of their correlation with the established subtitling guidelines, and their effect on the foreign audience.